A Case of Relapsing Polychondritis Initiating with Unexplained Fever - Kosuke Hirayama; Nozomi Iwanaga; Yasumori Izumi; Satoshi Yoshimura; Kazuhiro Kurohama; Mai Yamashita; Taichi Takahata; Ryuta Oku; Masahiro Ito; Atsushi Kawakami; Kiyoshi Migita (Case Reports in Medicine)
Relapsing polychondritis (RP) is a rare autoimmune disease affecting the multiple organ system. Here, we describe a case of RP initially presenting with high fever. The patient was referred to our hospital for further examination of fever of unknown origin (FUO). On admission, the patient reported dry cough in addition to fever. On physical examination, her red, swollen ears were noted, attributed on histology to inflammation with auricular perichondritis. She was diagnosed with RP and treated with oral prednisone (50 mg/day); her fever and auricular inflammation resolved. The patient no longer reported cough and body temperature returned to normal and the elevated levels of C-reactive protein (CRP) were normalized. In this case, identification of the origin of fever was a challenge because of unspecific symptoms; however, awareness of the systemic manifestations of RP may lead to the prompt diagnosis and therapeutic intervention.